Prevalência das disfunções temporomandibulares e sua correlação com o bruxismo em crianças - Costa, Joelma Magalhães da (2009)
Structural, functional and psychological factors characterize multifactority related the origin of temporomandibular disorders (TMD), which has been much researched and discussed because of the great controversies in this area. The objective of this study was to evaluate and associate the parafunctional habit of bruxism in children. An observational, cross-sectional study was carried out, with the participation of 104 children of private education institutes. To characterize the sample it was measured the height and weight; the determination of the presence and degree of severity of TMD was obtained by the Fonseca ´s anamnetic index; the diagnosis of bruxism was conducted by a clinical evaluation of a dentist and a physiotherapist. The data was analyzed using the program SAS for Windows v.9.1.3. The results showed that 50% of children had mild or moderate TMD, and 50% absence of TMD, and by associate the degrees of TMD of type mild and moderate with bruxism the boys was statistically significant (p<0.001) on the opposite sex and that being girls have 3.35 times more likely to obtain TMD. It was concluded that there is a relationship between TMD and bruxism in in both sexes studied, and the girls had a higher incidence of TMD, and the boys had relationship with increasing severity of TMD with bruxism, and in both sexes to present bruxism increases the chance of to be more vulnerable to the severity of TMD